Effect of the Brazilian process of thermal modification on the physical properties of Eucalyptus grandis juvenile wood - Djeison Cesar Batista (Maderas: Ciencia y Tecnología, 2018)
This study is a continuation of a previous study published in this journal, with the aim of evaluating the effect of the Brazilian industrial thermal modification process on some physical properties of Eucalyptus grandis juvenile wood. Flatsawn boards of juvenile wood were tested for four treatment levels: untreated and thermally modified wood at final cycle temperatures of 140 °C, 160 °C and 180 °C. Physical properties were assessed according to a standard of the Comisión Panamericana de Normas Técnicas and a method proposed by the specialized literature encompassing equilibrium moisture content (a measure of wood’s hygroscopicity), density (oven-dried and air-dried) and radial, tangential and volumetric swelling (from oven-dried to green moisture content). Thermally modified Eucalyptus grandis wood became less hygroscopic, more dimensionally stable (tangential and volumetric swelling) and less dense, even at the lowest temperature tested (140 °C), except for radial swelling, which did not differ from untreated wood.